ANALYSIS OF NORMATIVE BASE ON QUESTIONS OF ENLARGEMENT AGRICULTURAL COMMODITY PRODUCER (Journal of actual problems of jurisprudence, 2019)
In connection with the accession of Kazakhstan to the World Trade changed orientation in the agricultural policy, there is a needfor priority development of medium and large-scale commodity production, capable of producing competitive products. Agriculturalproduction in the country remains small-scale and this is one of the main reasons for its weak competitiveness. But among thepeasants formed a different opinion. They believe that the unification of the rural consumer co-operative for them is not economicallyprofitable. To reveal the nature of the problem is devoted to this article, by reviewing legislation to ensure that they impede orpromote the unification of small-scale agricultural producers